On-farm reproductive performance and breeding objective of sheep in six selected Districts of Tigray, Northern Ethiopia.. (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
The study was carried out in Atsibi Wonberta, Wukro Kilteawlaeo, Ofla, Alamata, Enderta and Degua Temben districts of Tigray Regional State of Ethiopia to assess the reproductive Performance and to describe the breeding objective of Sheep in the study area. A total of 12 peasant associations 2 from each district were selected randomly. A total of 180 households 30 from each district were selected randomly for the interview. Data were gathered through semi-structured questionnaire, focus group discussions and field observations. Data collected through questionnaire were described by descriptive statistics using JMP 5, 2002. In this study reproduction performance of sheep is assessed by their age at sexual maturity, age at first lambing, lambing interval, weaning age and lambing pattern. The overall estimated mean age at first lambing of ewes in the districts of Astibi-wonberta, Wukro-kilteawlaelo, Ofla, Alamata, Enderta and Degua-Tembien sheep was 18.15, 16.77, 16.7, 16.83, 17.77 and 16.77 months, respectively. The estimated mean lambing interval of highland sheep in Atsibi-Wonberta (9.6±0.7), Wukro-Kilteawlaelo (8.3±0.8), Ofla (6.3±0.7), Enderta (10.4±0.6), Deguatembien (8.4±0.5) and Afar (Elle) sheep in Alamata is 7.6±0.5 months respectively. The average weaning age of sheep in the study districts was three to six months. But, in Atsibi-wonberta (30%), Ofla (43.33%) and Enderta (36.67%) districts the average weaning age was greater than six months. Lambing of sheep was the highest during the months of December and November with an index value of 0.34 and 0.26, respectively. Generally the reproductive performance of sheep in this study area implies that the sheep breeds have acceptable age range for breeding though it is late compared to temperate breeds. In the study area for ram selection, farmers target was for breeding purpose and market value and fattening ability of the ram.